2016
DOI: 10.1007/s00198-016-3685-5
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal outcomes by peripheral quantitative computed tomography and dual-energy X-ray absorptiometry in adolescent girls with anorexia nervosa

Abstract: Summary We conducted the first comparison of dual-energy X-ray absorptiometry (DXA) and peripheral quantitative computed tomography (pQCT) outcomes in adolescent girls with anorexia nervosa. We observed deficits in bone density by both tools. pQCT assessments were associated with many of the same clinical parameters as have been previously established for DXA. Introduction Adolescents with anorexia nervosa (AN) commonly exhibit bone loss, but effects on bone geometry are less clear. We compared measures obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
(40 reference statements)
0
12
1
Order By: Relevance
“…However, one study assessed the distal tibia using pQCT, and reported lower trabecular, but higher cortical vBMD, in young women with AN compared with controls. AN girls in this study had a mean percent ideal body weight of 91%, and thus were not as low weight as in other studies [29*]. …”
Section: Assessment Of Bone Outcomes Including Use Of Novel Techniquesmentioning
confidence: 51%
“…However, one study assessed the distal tibia using pQCT, and reported lower trabecular, but higher cortical vBMD, in young women with AN compared with controls. AN girls in this study had a mean percent ideal body weight of 91%, and thus were not as low weight as in other studies [29*]. …”
Section: Assessment Of Bone Outcomes Including Use Of Novel Techniquesmentioning
confidence: 51%
“…Both the absolute BMD‐deficit and prevalence of low z‐score (below −2) in hip and lumbar spine, are similar to the findings in others cohorts comparable on age and duration of disease (Bachmann et al, ; Grinspoon et al, ; Hofman, Landewe‐Cleuren, Wojciechowski, & Kruseman, ; Winston, Alwazeer, & Bankart, ). Furthermore, patients with similar age at debut of disease and BMI at baseline, but with shorter duration of disease, are reported to have higher BMD (DiVasta et al, ; Levy‐Shraga et al, ; Misra et al, ). Thus, our findings support the notion that the adverse effect of malnutrition on bone progresses with increasing duration of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional status in terms of extremes of underweight and overweight have adverse consequences for bone accretion and development of optimal bone strength. Adolescents with anorexia have low bone density and reduced strength compared to normal weight peers, and these effects can be long lasting (79,80). At the other end of the spectrum, children with obesity have greater bone mineral content and density and greater cortical thickness than non-obese children (81).…”
Section: Diet and Nutritional Statusmentioning
confidence: 99%